Not so rational: A more natural way to understand the ANS. (15th December 2021) - Hecht, Eli; Mills, Tracey; Shin, Steven; Phillips, Jonathan
Abstract: In contrast to Clarke and Beck's claim that that the approximate number system (ANS) represents rational numbers, we argue for a more modest alternative: The ANS represents natural numbers, and there are separate, non-numeric processes that can be used to represent ratios across a wide range of domains, including natural numbers.